Penumbuh Rambut Hair Tonic Aloe vera secara in vivo pada Kelinci - Warditiani, Ni Kadek; Armita Sari, Pande Made Nova; Maha Dewi, Ni Kadek Santi; Natalia Kote, Jessica Christy (Jurnal Farmasi Udayana, 2024)
Hair loss is an event of hair loss from the scalp that occurs regularly. However, hair loss becomes a problem if the amount of loose hair exceeds the normal limit. A hair tonic serves as a base for taking care of the hair and scalp. Aloe vera is often used as a hair care ingredient. In addition, this natural ingredient has the function of accelerating hair growth and reducing hair loss. Another natural ingredient used in making hair tonic is patchouli oil, which of course has a distinctive smell. The intention of this examine became to assess the effectiveness of a mixture of aloe vera and patchouli oil as a hair tonic for hair growth. In this study using a rabbit ridge which will be divided into 5 treatment groups with each different treatment. The treatment group that was given consisted of normal control, negative control (basic hair tonic), comparison control (hair tonic on the market), treatment control 1 (hair tonic given every 2 days) and treatment control 2 (hair tonic given 3 times). once a day). The test results were carried out by measuring the length of the rabbit's hair every 7 days for 21 days. One Way ANOVA and the LSD test were then used to statistically test the collected data. The study's findings demonstrated that a hair tonic consisting of aloe vera and patchouli oil, administered once every three days, significantly (p<0.05) accelerated the development of hair in rabbits.